The Regulations Development of Objection Against the Indonesia Competition Commission (KPPU) Decision - Aidi, Zil (Sekolah Tinggi Hukum Bandung, 2023)
This research aims to analyze the regulation development of objection against the KPPU's decision after the issuance of the Supreme Court Regulation (PERMA) No. 3/2021 and its implementation. The research is descriptive with normative juridical type, using primary data through interviews and secondary data through library research, using qualitative analysis and logical deduction reasoning. There are differences in absolute competence, timeframe, and case examination between PERMA No.3/2021 with previous arrangements. This PERMA has been implemented at the Commercial Courts of Central Jakarta, Surabaya, and Medan. In addition, the transfer of absolute competence to the Commercial Court makes the performance of the KPPU's litigation team more efficient because it no longer needs to travel to many cities to face objections, considering the Commercial Court is only domiciled in 5 regions throughout Indonesia. Commercial Court judges should also understand business law better and be expected to produce quality decisions.